Cryoballoon Catheter Ablation in Atrial Fibrillation - Cevher Ozcan; Jeremy Ruskin; Moussa Mansour (Cardiology Research and Practice)
Pulmonary vein isolation with catheter ablation is an effective treatment in patients with symptomatic atrial fibrillation refractory or intolerant to antiarrhythmic medications. The cryoballoon catheter was recently approved for this procedure. In this paper, the basics of cryothermal energy ablation are reviewed including its ability of creating homogenous lesion formation, minimal destruction to surrounding vasculature, preserved tissue integrity, and lower risk of thrombus formation. Also summarized here are the publications describing the clinical experience with the cryoballoon catheter ablation in both paroxysmal and persistent atrial fibrillation, its safety and efficacy, and discussions on the technical aspect of the cryoballoon ablation procedure.